SAFE PERFORMANCE OF WORKS IN CONSTRUCTION AND HOUSING AND COMMUNAL SERVICES USING THE ORIGINAL SCAFFOLDING DESIGN - Abrakitov, V.; Ivashchenko, M.; Moroz, M.; Nikitchenko, O. (Municipal economy of cities. Series: «Economy science», 2024)
Our development relates to construction, namely scaffolding and scaffolding used when working at height. It is intended for fencing the work area when carrying out various types of work, for example, when performing brickwork from scaffolding. In construction, where safety and efficiency play a crucial role, the correct selection and use of scaffolding are integral to every successful project. We have proposed a patent-protected solution. It is a scaffolding railing consisting of vertical support posts hinged with horizontal crossbars, characterised by the fact that each support post is made in the form of a telescopic connection of pipes of different diameters with the possibility of extending them from each other and is fixed with the help of an existing locking device. The hinge connection of horizontal crossbars with them, except the upper row of such bars that are railing, is made in random order, for example, by attaching a hinge to the upper end of the upper tube of the smallest diameter, and is carried out using additional ring elements mounted on the corresponding telescopic connecting tubes. The inner diameter of each of these annular elements, exceeding the outer diameter of the tube on which it is mounted, is less than the outer diameter of the next subordinate telescopic tube. Thus, it can move only vertically in a telescopic connection within this and above pipes. It makes it possible to support each of the ring elements with horizontal crossbars attached to them under their weight at a certain level of height of the vertical support post, determined by the height of the underlying tube of the telescopic connection. At the same time, the lower horizontal crossbar is hinged to the ring element of the largest diameter, put on the lower tube of the telescopic connection, and rested directly on the working flooring made in the form of a sideboard. The proposed device is not technically complex to implement. Its use increases the workers’ productivity, improves the working conditions, and ensures the safety of various construction works.